A People & Purpose Approach to Humanitarian Data Information Security and Privacy. (2016) - Chan, Jennifer; Bateman, Lauren; Olafsson, Gisli
Abstract: With the advent of new digital technologies and increasing capabilities to share pre-existing information streams, the role of data information security and privacy has become a challenging and pressing topic in the humanitarian sector. In recognition of the need for policies, protocols, and practices, we present one view on a responsible data approach with emerging protocols and perspective on its implementation. We 1) present a brief overview of existing efforts with a focus on data-sharing and its role in service-oriented operational decision-making, 2) describe a people-purpose driven approach for understanding data sharing as it relates to information security and privacy processes, and 3) provide early reflections on the challenges to implementing this framework and areas for future development.